Road Damage Geographic Information System In Sukosari Village - Rosidah, Zea (YHMM PUBLISHING, 2024)
One of the mapping technologies that are widely used today is the geographic information system, geographic information systems are often also called GIS (Geographic Information system) is a mapping technology in the form of a computer-based information system, which is designed to work using data that has special information or spatial references. Roads are land transportation facilities that have an important role in the field of transportation, connecting cities to cities, cities to villages, and villages to villages. Road damage has an impact on the safety and comfort of road users. Until now, there has never been any road damage in Sukosari Village caused by the conflict between Pringsewu and Pesawaran districts. Therefore, it is necessary to collect new information from the community about the current condition of the road so that village officials can immediately repair it because input from the community can make it easier for the village to make further improvements. For the problems mentioned above, a geospatial damage information system was created in the hope that the government can use the clustering method to determine the damage to level roads in Sukosari District. One of the methods used in this system is waterfall or also called waterfall. The information collected for this study came from the Sukosari website. Based on the results of the accuracy method, the waterfall used in this study is 100% accurate in terms of presentation of its suitability. The investigation of this method into the damage to the road geographical information system in Sukosari village clarifies that there are problems in the system that are not addressed in the research so that the system functions as planned.